2015
DOI: 10.4049/jimmunol.1402568
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cell–Derived IL-21 and Deprivation of CD40 Signaling Favor the In Vivo Development of Granzyme B–Expressing Regulatory B Cells in HIV Patients

Abstract: IL-21 can induce both plasma cells and regulatory B cells. In this article, we demonstrate that untreated HIV patients display CD4+ T cells with enhanced IL-21 expression and high in vivo frequencies of regulatory B cells overexpressing the serine protease granzyme B. Granzyme B–expressing regulatory B cells (GraB cells) cells from HIV patients exhibit increased expression of CD5, CD43, CD86, and CD147 but do not produce IL-10. The main functional characteristic of their regulatory activity is direct granzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 52 publications
6
68
1
3
Order By: Relevance
“…This causes phosphorylation of tyrosine residues on IL-21R/γc, providing docking sites for STAT proteins and other signaling molecules (26). On recruitment, STATs are phosphorylated and form homodimers or heterodimers, which translocate into the nucleus and modulate expression of the target genes (27), which regulate B-cells, such as B-cell-induced maturation protein-1 (Blimp-1) (28), B-cell lymphoma (BCL)-6 (29), activation-induced cytidine deaminase (AID) (30), granzyme (31), somatic hypermutation (SHM) (32), paired box 5 (Pax5) (33), X-box-binding protein 1 (XBP-1) (34), and Bim (35). IL-21 mediates B-cell proliferation, immunoglobulin (Ig) production, and apoptotic functions mainly through the potent effects of STAT3 and/or STAT1 activation but also, to a lesser extent, through STAT4 and STAT5 (3639) (Figure 1).…”
Section: Il-21 Signaling Pathway In B-cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This causes phosphorylation of tyrosine residues on IL-21R/γc, providing docking sites for STAT proteins and other signaling molecules (26). On recruitment, STATs are phosphorylated and form homodimers or heterodimers, which translocate into the nucleus and modulate expression of the target genes (27), which regulate B-cells, such as B-cell-induced maturation protein-1 (Blimp-1) (28), B-cell lymphoma (BCL)-6 (29), activation-induced cytidine deaminase (AID) (30), granzyme (31), somatic hypermutation (SHM) (32), paired box 5 (Pax5) (33), X-box-binding protein 1 (XBP-1) (34), and Bim (35). IL-21 mediates B-cell proliferation, immunoglobulin (Ig) production, and apoptotic functions mainly through the potent effects of STAT3 and/or STAT1 activation but also, to a lesser extent, through STAT4 and STAT5 (3639) (Figure 1).…”
Section: Il-21 Signaling Pathway In B-cellsmentioning
confidence: 99%
“…Interleukin-21 can induce BCR-stimulated human B-cells to differentiate into granzyme B-expressing cytotoxic cells (GrB) in a STAT3-dependent manner in the absence of a CD40 signal (31, 77, 8688). GrB + B-cell numbers are dependent on IL-21 production, and increasing doses of anti-IL-21 decreased the number of GrB-expressing B-cells in co-culture systems (78).…”
Section: Granzyme B Production By B-cellsmentioning
confidence: 99%
“…Interestingly, it has been reported in humans that granzyme B + B cells accumulated specifically in tissues and have been suggested to play a critical role in early antiviral immune responses, in the regulation of autoimmune mechanisms, and in cancer immunosurveillance (45)(46)(47). Additionally, it has recently been shown that BCR and IL-21 signaling without an efficient CD40-CD40L ligation leads to the generation of granzyme B + B cells that induce immune dysfunction in solid tumor eradication (45,(48)(49)(50) or in HIV patients (51). Therefore, in our model, the regulatory B cells when they reencountered the alloantigens in the spleen and because of their defect in CD40 signaling may lead to the generation of granzyme B + plasmablast-like regulatory B cells that accumulated particularly in the graft tissue.…”
Section: Igmmentioning
confidence: 99%
“…It was also shown that IL-21 signaling affects the interactions between T cells and B cells and repeal protective humoral immunity to Malaria (45). Interestingly, recent studies have demonstrated that despite the fact that IL-21 can provide apoptotic signals for the B cells, it can also induce BCR-stimulated human B cells to differentiate into Granzyme B-expressing cytotoxic cells against tumor cells in the absence of CD40 signal in a STAT3-dependent fashion (46)(47)(48)(49). Based on these conflicting studies, it is believed that IL-21 may have a role in early stages of infection by induction of B cell proliferation and amplification of the humoral immune response while inducing apoptosis of B cells as a mechanism for eliminating inappropriately activated autoreactive B cells (24).…”
Section: Il-21 Induces the Differentiation Of B Cells Into Plasma Celmentioning
confidence: 98%